Kochankowie i klamcy - Beauman, Sally; Dobrzanska-Gadowska, Anna. (Warszawa : Swiat Ksiazki, 2004)
Polish translation of "Lovers and liars". An absorbing bestseller novel about former lovers who become partners in a criminal investigation.
Translation of: Lovers and liars.
Keywords: Investigative reporting -- Fiction